Fast Formation of Surface Oxidized Zn Nanorods and Urchin-Like Microclusters - R. López; T. Díaz; G. García; E. Rosendo; R. Galeazzi; A. Coyopol; H. Juárez; M. Pacio; F. Morales; A. I. Oliva (Advances in Materials Science and Engineering)
Entangled Zn-ZnO nanorods and urchin-like microstructures were synthesized by the hot filament chemical vapor deposition technique at 825 and 1015°C, respectively. X-ray diffraction results showed a mixture of ZnO and Zn phases in both nanorods and urchin-like structures. The presence of Zn confirms the chemical dissociation of the ZnO solid source. The Z-ZnO nanorods with diameter of about 100 nm showed dispersed-like morphology. The urchin-like structures with micrometer diameters exhibited porous and rough morphology with epitaxial formation of nanorods.